2003
DOI: 10.1002/jbm.a.20062
|View full text |Cite
|
Sign up to set email alerts
|

Numerical failure analysis of glass‐fiber‐reinforced composites

Abstract: Abstract:The purpose of this work was to propose a new numerical model for glass-fiber-reinforced composites. The proposed numerical model was constructed with orthotropic shell, isotropic shell, and beam elements representing glass fiber cloth, silica filler, and the remaining matrix resin, respectively. The proposed model was applied to failure analysis under three-point bending conditions. The validity of the numerical model was checked through comparisons with experimental results. Four types of specimens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…Generally glass fibers with diameters ranging from 10 to 17 μm are used for industrial fiber-reinforced plastic materials 33) . With increasing glass fiber diameter (7,10,13,16,20,25,30 and 45 μm), the flexural strengths of FRC of 30 vol% fiber content increased except for the FRC with 45 μm diameter fibers 33) . Water sorption and solubility, which cause dimensional change, are important factors for denture base resin.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Generally glass fibers with diameters ranging from 10 to 17 μm are used for industrial fiber-reinforced plastic materials 33) . With increasing glass fiber diameter (7,10,13,16,20,25,30 and 45 μm), the flexural strengths of FRC of 30 vol% fiber content increased except for the FRC with 45 μm diameter fibers 33) . Water sorption and solubility, which cause dimensional change, are important factors for denture base resin.…”
Section: Discussionmentioning
confidence: 96%
“…UHMWP fibers are biocompatible and possess a high degree of stiffness, toughness, and strength 11,21,22) . The mechanical properties of FRC are dependent upon the composition of the fiber, fiber orientation, the ratio of fiber to resin, and the adhesion between the fiber and resin matrix 11,[23][24][25] . A hybrid FRC is obtained with two or more different types of fibers in a single matrix and has a better combination of properties than composites containing only a single fiber type 10) .…”
Section: Introductionmentioning
confidence: 99%
“…We selected the above‐mentioned ratio of UDMA and TEGDMA, because it was difficult to preparing dental composite due to the heterogeneous dispersion of silica fillers into resin mixture when resin mixture consisting other monomer ratio, for example, 80 mol % UDMA and 20 mol % TEGDMA or 20 mol % UDMA and 80 mol % TEGDMA. Silica particles of uniform particle size with 7‐μm mean diameter (Tatsumori Ltd., Tokyo, Japan) were used as filler materials of composite according to the previous paper 25. The coupling agent used was γ‐methacryloxy propyltrimethoxysilane (γ‐MPTS, Shin‐Etsu Corp., Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that aramid fibers have been shown to increase the impact strength of polymethyl methacrylate (PMMA) resin significantly and to enhance the fracture resistance of acrylic resin [17][18][19] . The fiber type, the diameter and the length of the fiber, the weight ratio of resin to fiber, the location and orientation of the fibers in the resin matrix, the adhesion between the fibers and the resin matrix and the pre-impregnation of fibers play a crucial role in the reinforcing effect of the resin matrix [20][21][22] . There have been many studies on the effects of the concentration and orientation of glass fibers on the reinforcement of denture base resin [23][24][25][26] .…”
Section: Introductionmentioning
confidence: 99%